Growth performance of oil palm seeds of different vigor in pre-nursery / M.P. Siti Atikah and F.Y. Tsan - M.P., Siti Atikah; Tsan, F.Y (Universiti Teknologi MARA, Perlis, 2017)
Seeds are products due to combination of parental genetic materials and hence, are different from one another, especially with outcrossing species, for example oil palm. Despite controlled pollination to produce desired hybrid of Tenera, oil palm seeds can still be greatly different in vigor expressed as the speed of seed germination. In this study, seeds of two different vigor, namely those germinated fast within three to five days (vigorous seeds) and those that took more than 14 days to germinate (seeds of low vigor), were studied for their seedling growth performance and culling rate in pre-nursery. The experiment was conducted at Tun Razak Agricultural Research Centre, Felda Agricultural Services Sdn. Bhd., Jengka, Pahang. For each type of seeds, 300 germinated seeds grown in six 50-cell plug trays in peat moss as the growth media using semifloat system were randomly selected as test materials. This experiment was based on a Completely Randomized Design (CRD) with six replicates. The results obtained showed that there was generally no significant difference in plant height, leaf number, length of foliage and relative chlorophyll content between seedlings raised from seeds of the two different qualities throughout the pre-nursery period of three months. However, vigorous seeds developed into seedlings with significant better growth performance in terms of width of foliage and stem diameter and had relatively lower culling rate as compared to those grown from seeds that took more than 14 days to germinate. Therefore, the use of vigorous seeds is beneficial in production of oil palm planting materials but seeds with low vigor were still useful in providing cheaper planting stock to planters.